2022
DOI: 10.2991/assehr.k.220129.059
|View full text |Cite
|
Sign up to set email alerts
|

EFA of Pedagogic Competence Instrument to Measure Teacher Performance

Abstract: The purpose of this research was to determine the feasibility of the instrument in terms of construct validity test of exploratory factor analysis (EFA) on pedagogic competence instrument to measure the teachers" per-formance. The focus was on describing the decisions made in EFA. The method used in this research was the instrument development with a response approach. The results showed that the instrument has been de-clared feasible in terms of: 1) the index of the distance comparison between the correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The influence and the important role of teacher pedagogic competence on the quality of education can be seen from the results of research by experts. Several studies, among others, were conducted by Prihono et al [19] who in his research concluded that pedagogic competence has a positive effect on lecturers' academic performance. Channa and Sahito [20] in a study found that teacher pedagogic competence had a positive effect on student learning motivation.…”
Section: Introductionmentioning
confidence: 99%
“…The influence and the important role of teacher pedagogic competence on the quality of education can be seen from the results of research by experts. Several studies, among others, were conducted by Prihono et al [19] who in his research concluded that pedagogic competence has a positive effect on lecturers' academic performance. Channa and Sahito [20] in a study found that teacher pedagogic competence had a positive effect on student learning motivation.…”
Section: Introductionmentioning
confidence: 99%